PENCAHAYAAN DAN WARNA DI KAMAR ASRAMA HAJI: DAMPAKNYA TERHADAP KESEJAHTERAAN SUBJEKTIF PENGUNJUNG - Putri Ahmadina; Mahendra Wardhana (ADISAM PUBLISHER, 2025)
The interior of a space plays a significant role in shaping the subjective well-being of its occupants, with lighting and color serving as key elements that influence comfort, mood, and functional efficiency. Hajj dormitories, as temporary accommodations for pilgrims and visitors, often suffer from inadequate lighting and color schemes that fail to support comfort, potentially diminishing the overall quality of the occupants' experience. This study analyzes visitor preferences for lighting and color in Hajj dormitory bedrooms and their impact on subjective well-being. Through systematic observation and analysis, the research identifies how lighting and color choices affect users’ psychological responses. The findings reveal that dim or non-adjustable lighting reduces comfort and usability, while overly vibrant or monotonous color schemes disrupt emotional balance, creating an unpleasant atmosphere. As a solution, this study recommends the implementation of adaptive lighting systems that cater to users’ varying needs, along with a more calming and positive color palette. By applying the principles of Positive Design, Hajj dormitories can be redesigned to enhance both the physical and psychological well-being of their occupants. These findings can also be applied to other communal living spaces to improve overall comfort and user experience